Analysis of the Characteristics of Evacuation Information Acquirers from Online Media based on Typhoon Victim Data - Nagayuki Saito; Nao Fukushima; Etsuko Jifuku; Yumiko Takabe; Yasuhiro Nakajima; Kiyotaka Eguchi (International Telecommunications Society (ITS), 2020)
In recent years, many natural disasters have occurred in Japan. As a means for providing information in the event of such a disaster, online media has emerged as a valuable resource. In this study, we analyze the online-media usage tendencies of victims evacuating from Typhoon No. 19 through questionnaire data. The results of cluster analysis and comparative analysis of evacuees' attributes demonstrate that acquiring evacuation information from online media is an information-seeking action similar to obtaining information from one's friends, acquaintances, and neighbors. Such behavior is a self-exploratory information gathering behavior. Therefore, as regards the direction of online media utilization in future of natural disasters, it should be an effective means for to collecting local disaster information from users; then this information can be utilized for disaster countermeasures.
Keywords: 330; online media; natural disaster; evacuees; evacuation; information-seeking